Análisis de la calidad del sistema de distribución de energía eléctrica del hospital Sagrado Corazón de Jesús del cantón Quevedo - Aguirre Montoya, Ángel Heriberto (2016)
The object of research of this project is focused on determining whether the power supply of the Sacred Heart Hospital of Jesus of Canton Quevedo meets quality standards regulated by the ARCONEL through network analyzer Fluke 1744 device that allows us to analyze the parameters disturbances that can interfere with the proper conduct of this important health house in our town. Similarly enters analyzes the current state of electrical installations, chargeability distribution transformer, panels and load centers, sizing protection, thermal limits of the conductors and distribution of the areas supported by generators seeking to detect flaws that interfere with the operation of equipment using electricity. Rising electricity infrastructure runs in order to capture the distribution circuits from the mains supply in medium voltage to the load centers with power analysis / installed capacity ratio proposing improvements to be made.